The German Freemason settlers and the development of Freemasonry in Banat in the 18th and 19th centuries - Attila Carol Varga (Swedish Journal of Romanian Studies)
This study underlines the fact that Freemasonry, brought to Banat by the Austrian settlers, did not leave this area as an isolated provincialism. It was in direct contact with the Central European elite, exchanging ideas and experiences. At that time, Freemasonry facilitated the access of representatives of the small and middle bourgeoisie, merchants, entrepreneurs, military and civil servants, creating a real community outside the traditional structures. This was also the case in Banat in the 19th century. The Masonic lodges of this period continued the inherited Masonic tradition, carrying on the elitist spirit brought by the Austrian colonists in the previous period. In the 19th century, two lodges in the Mountains Banat, continued this Austrian Masonic tradition. These were the Lodge ‘Glück auf’ in Oraviţa and the Lodge ‘Licht und Wahrheit’ in Reşiţa. Both contributed significantly to the complex process of modernisation of Banat society, but also to the success of the Romanian national movement during the Austro-Hungarian Monarchy.